2013
DOI: 10.1200/jco.2013.31.4_suppl.289
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative radiotherapy for gallbladder cancer.

Abstract: 289 Background: Gallbladder cancer (GBC) is a relatively uncommon malignancy with high recurrence rate and poor prognosis, even after curative resection. Although postoperative radiotherapy (RT) has been tried to improve the poor results of surgery alone, the benefit of postoperative RT for GBC is still a matter of debate. The present study aimed to evaluate the effect of postoperative RT on locoregional control (LRC), disease-free survival (DFS), and overall survival (OS) in patients with GBC. Methods: Betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…15 The 24 observational studies consisted of 4 retrospective cohort studies, [16][17][18][19] with a total of 1772 patients; two PBCS (2867 patients), 20,21 and 18 retrospective PS (1130 patients). 2,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] In all this represents a total of 55 studies and 9887 patients with GBC treated with curative surgical intent.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…15 The 24 observational studies consisted of 4 retrospective cohort studies, [16][17][18][19] with a total of 1772 patients; two PBCS (2867 patients), 20,21 and 18 retrospective PS (1130 patients). 2,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] In all this represents a total of 55 studies and 9887 patients with GBC treated with curative surgical intent.…”
Section: Resultsmentioning
confidence: 99%
“…In a series of patients resected with curative intent, some of whom underwent adjuvant CT or adjuvant CRT, we verified improvement of OS in patients with R1 (HR: 0.38 [0.23, 0.65]) vs. surgery alone (HR: 0.26 [0.15, 0.43]). 35 In other series, it was found that "surgical margin" is a factor of poor prognosis; as the Kasumova study (OR: 1,207 [0.066, 1.367]) 23 Kim's (HR: 6,981 [2,378,20,491], p < 0.001) 24 ; that of Jeong who reported 40% and 14% SV at 5 years for R0 and R1 respectively (p = 0.001) 28 ; and those of Yang and Ye, who reported OS in stage IV patients at 1, 3 and 5 years of 14.2%, 7.2% and 7.2%; and 71.4%, 9.5%, and 4.8% respectively. 32,33 A small number of patients, who underwent extended cholecystectomy, in which the results of CRT followed by CT were analyzed, showed that the median OS in patients with R0 and R1 was 46 and 23 months respectively 26 (type 4 treatment and prognosis studies).…”
Section: Effectiveness Of Adjuvant Treatments In Positive Surgical Mamentioning
confidence: 90%
See 3 more Smart Citations